Videoscopic ilioinguinal lymphadenectomy for groin lymph node metastases from melanoma. Issue 8 (5th May 2016) - Sommariva, A; Pasquali, S; Cona, C; Ciccarese, A A; Saadeh, L; Campana, L G; Meroni, M; Rossi, C R
Abstract: Background: Groin lymph node dissection for melanoma is burdened by high postoperative morbidity. Videoscopic lymphadenectomy may lower the incidence of complications, including infection, dehiscence and lymphoedema. This pilot study aimed to investigate the feasibility and postoperative outcomes of videoscopic ilioinguinal lymphadenectomy in patients with inguinal nodal melanoma metastases. Methods: Patients with inguinal nodal metastases, with either a positive sentinel lymph node biopsy or clinically positive nodes from melanoma, were enrolled. Inguinal dissection was performed via three ports. Iliac dissection was obtained through a preperitoneal access. Intraoperative and postoperative data were collected. Results: Of 23 patients selected for 24 procedures, four needed conversion to an open procedure. Median duration of surgery was 270 (i.q.r. 245–300) min. Wound-related postoperative complications occurred in four patients, although only one needed further intervention. The median number of excised lymph nodes was 21 (i.q.r. 15–25). After a median follow-up of 18 months, regional lymph node recurrence was observed in two patients. Conclusion: Videoscopic ilioinguinal lymphadenectomy for melanoma groin lymph node metastases is technically feasible, safe, and associated with acceptable morbidity and oncological outcome. Abstract : More support for videoscopic surgery